COVID-19 vaccination in psoriasis patients receiving systemic treatment: A prospective single-center study - Lodde, Georg Christian; Krefting, Frederik; Placke, Jan-Malte; Schneider, Lea; Fiedler, Melanie; Dittmer, Ulf; Becker, Jürgen Christian; Hölsken, Stefanie; Schadendorf, Dirk; Ugurel, Selma; Sondermann, Wiebke (Frontiers in Immunology, 2023)
Background The rate of seroconversion after COVID-19 vaccination in patients with moderate to severe psoriasis requiring systemic treatment is poorly understood. Objectives The aim of this prospective single-center cohort study performed between May 2020 and October 2021 was to determine the rate of seroconversion after COVID-19 vaccination in patients under active systemic treatment for moderate to severe psoriasis. Methods Inclusion criteria were systemic treatment for moderate to severe psoriasis, known COVID-19 vaccination status, and repetitive anti-SARS-CoV-2-S IgG serum quantification. The primary outcome was the rate of anti-SARS-CoV-2-S IgG seroconversion after complete COVID-19 vaccination. Results 77 patients with a median age of 55.9 years undergoing systemic treatment for moderate to severe psoriasis were included. The majority of patients received interleukin- (n=50, 64.9%) or tumor necrosis factor (TNF)-α inhibitors (n=16, 20.8%) as systemic treatment for psoriasis; nine patients (11.7%) were treated with methotrexate (MTX) monotherapy, and one patient each received dimethyl fumarate (1.3%), respectively apremilast (1.3%). All included patients completed COVID-19 vaccination with two doses over the course of the study. Serum testing revealed that 74 patients (96.1%) showed an anti-SARS-CoV-2-S IgG seroconversion. While all patients on IL-17A, -12 or -12/23 inhibitors (n=50) achieved seroconversion, three of 16 patients (18.8%) receiving MTX and/or a TNF-α inhibitor as main anti-psoriatic treatment did not. At follow-up, none of the patients had developed symptomatic COVID-19 or died from COVID-19. Conclusions Anti-SARS-CoV-2-S IgG seroconversion rates following COVID-19 vaccination in psoriasis patients under systemic treatment were high. An impaired serological response, however, was observed in patients receiving MTX and/or TNF-α inhibitors, in particular infliximab.